Analysis of Antimony Removal with Modified Activated Carbon Using Response Surface Methodology - Tapiory, Jesica; Prasetya, Agus; Astuti, Puji (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2024)
Antimony (Sb) is a metal compound that can cause health problems when it accumulates in the food chain and becomes toxic to the ecosystem. Industrial activities have driven Sb contamination of water, including surface water. At the same time, some drinking water treatment plants (DWTP) use surface water as raw water, which requires adequate treatment. An invention of cheap and accessible technology is needed for developing countries such as Indonesia; hence, this study presents research on modified activated carbon with iron sulfate and manganese sulfate to create a better adsorbent from commercial granular activated carbon (GAC). The independent variables in this study included the type of adsorbent (GAC and GACMF), acidity level, and dosage. Response surface methodology was implemented for the analysis. According to the study, it was found that the optimum state of non-modified GAC for Sb removal appears at pH 3 and a dosage of 0.03 g L-1. In contrast, the presence of modified GAC was more effective for Sb removal with an optimum pH of 6 and a dosage of 0.057 g L-1 for GACMF. This research suggests that GACMF is preferable for DWTP because the optimization shows that GACMF is optimized in a neutral state; therefore, additional chemicals are unnecessary to achieve a neutral acidity state.